SPE Annual Technical Conference and Exhibition 2014
DOI: 10.2118/170960-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Myth of Sweet Spot Exploration

Abstract: Enormous effort and expense is put forth to explore for "sweet spots", but is it worthwhile? Is it even possible or, more importantly, a good business decision to attempt to explore for sweet spots? It is contended that, at a minimum, the vast majority of sweet spot exploration activity is wasted time and effort. Chasing the "golden carrot" leads to poor decision making and the investment of vast sums of capital in non-economic plays and basins. While the term "sweet spot" has taken on several d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…This third period is explained by technological advances in completion strategy (longer horizontal drains, more fracturing stages, and optimization of proppant concentration). The same three periods are found in the global (conventional and unconventional) US gas production for the 2008-2015 period (Mills 2015). Production is increasing continuously despite an initial reduction in the number of rigs (1,600 to 1,000) in late 2008 after the subprime crisis and then a second reduction in 2012 after the fall of gas price (fewer than 400 rigs).…”
Section: Drillingsupporting
confidence: 59%
“…This third period is explained by technological advances in completion strategy (longer horizontal drains, more fracturing stages, and optimization of proppant concentration). The same three periods are found in the global (conventional and unconventional) US gas production for the 2008-2015 period (Mills 2015). Production is increasing continuously despite an initial reduction in the number of rigs (1,600 to 1,000) in late 2008 after the subprime crisis and then a second reduction in 2012 after the fall of gas price (fewer than 400 rigs).…”
Section: Drillingsupporting
confidence: 59%
“…Having the correlation between TOC and shale mechanical properties, seismic data can identify the presence, geometry, and TOC content source rock to identify the sweet spot. Although the sweet spot has some potential pitfall and even unrealizable as pointed out by Haskett (2014), more efforts should be spent to correlate the production potential of shale with its mechanical and maturation characteristics.…”
Section: Geomechanics In Reservoir Characterizationmentioning
confidence: 99%
“…Appraisal of shale gas resource plays remains difficult and expensive despite the large number of wells that have been drilled, cored and tested. For example, Haskett (2014) suggested that over ten pilot wells may be needed to have 90% confidence that the results are representative of the shale gas play. Also, up to 100 wells may be needed before optimal production efficiency has been reached and production costs minimized (Haskett, 2014).…”
Section: Introductionmentioning
confidence: 99%